Ataxia Telangiectasia: A Single Center Experience in a Decade - Lobna Mansour; Magd A. Kotb; Ezzat El Sobky; Lamia Tarek; Walaa El Naggar; Mona Ahmed Kamel (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Ataxia Telangiectasia (A-T) is a rare neurodegenerative disorder that affects a number of different systems of the body. Aim of the work: To identify the spectrum of clinical presentations of children with A-T. Methods: Retrospective cohort study of data of 35 children with confirmed diagnosis of A-T. Results: A-T clinical spectrum was diverse with two distinct presentations according to age of onset of symptoms; classic early onset among 29 (82%) (mean age± SD= 2.9 ± 0.63 years) and variant late in 6 (17%) (mean age± SD=9.83 ± 1.34 years). In early onset A-T the leading presentations were classic; ataxia in 100%, telangiectasis (100%), dysarthria (62%), cerebellar atrophy (58%), repeated sinopulmonary infections (48%), autoimmune vitiligo in one child, but not peripheral neuropathy or postural scoliosis. While among those with late onset A-T, the leading presentations were extrapyramidal manifestations and dystonia in (66.6%), late development of ataxia (100%), telangiectasis (50%), dysarthria (66.6%), repeated sinopulmonary infections (16.6%), cerebellar atrophy (16.6%) and peripheral neuropathy (50%). All 35 (100%) had elevated alfa fetoprotein, 74% had reduced IgE levels and 68% had reduced IgA levels. Acute lymphoblastic leukemia (ALL) complicated the course of 17.2% and 16.6% of early and variant late onset A-T respectively, and preceded the onset of ataxia among 50% of affected cases. Conclusion: Ataxia telangiectasia is a rare neurologic disease with various clinical presentations. A-T clinical spectrum is diverse with two distinct presentations according to age of presentation: classic early onset and variant late onset. Immune dysregulation is more pronounced among the early onset group. ALL might be the initial presentation of A-T that precedes the onset of ataxia and of telangiectasis.